İlköğretim Dersliklerinde Aydınlatma Enerjisi Yönetiminde Yönlere Göre Uygun Cephe Seçeneklerinin Belirlenmesi - Kutlu, Rana; Küçükdoğu, Mehmet (My University, 2009)
Bu doktora çalışmasında, bir derslik hacminde iklimsel ve görsel konfor koşulları açısından, yöne bağlı olarak en uygun cephe düzenlemelerinin elde edilmesi amaçlanmaktadır. Bu amaçla, Bayındırlık ve İskan Bakanlığı’nın tip ilköğretim okulu projelerinin derslik hacimlerinde uyguladığı mevcut cephe düzeni ile iklimsel ve görsel konfor koşulları açısından yönlere göre geliştirilen uygun cephe düzenlemelerinin yapma aydınlatma enerjisi tüketimleri açısından bir karşılaştırması yapılmıştır. Dersliklerde sağlanan günışığı aydınlık düzeyleri Radiance simulasyon programı aracılığı ile hesaplanmıştır. İlköğretim okulunun İstanbul’da olduğu düşünülerek, 2006-2007 öğretim yılı boyunca ve okulların açık olduğu saatler için, günışığı hesaplamaları yapılmıştır. Günışığı hesaplamalarında mevcut kabuktan elde edilen değerlere bağlı olarak her ayı karakterize eden gün belirlenmiş ve öneri kabuk alternatifleri için yapılan günışığı hesaplamaları bu kabule göre karakteristik gün için yapılmıştır. Enerji etkin tasarım ilkelerine göre yönlere bağlı geliştirilen öneri kabuk alternatiflerinde gölgeleme istenen dönem göz önünde bulundurularak, dış gölgeleme araçları uygulanmıştır. Gölgeleme araçlarının pozisyonları sabit ve hareketli olmak üzere iki şekilde kabul edilmiştir. Mevcut kabuk, sabit gölgeleme aracına sahip öneri kabuk 1 ve hareketli gölgeleme aracına sahip öneri kabuk 2 alternatiflerinin hacimde sağlanan günışığı değerlerine bağlı olarak yapma aydınlatma enerji yükleri belirlenmiştir. Kabuk alternatiflerinin yönler değişkenine bağlı olarak, hacimde elde edilen enerji yükleri karşılaştırılmıştır. Sonuçlar aydınlatma ekonomisi ve görsel konfor koşulları açısından değerlendirilerek uygun çözüm belirlenmeye çalışılmıştır.

The concepts of sustainability and sustainable development take into account life conditions of future generations and environmental values while meeting contemporary needs and to this end, they entail the creation of healthy environments for human beings in the relationship established between environment, economy, and technology. Sustainability also requires an accurate and planned use of natural light, that is, daylight in the context of energy efficient lighting design. Changes and developments that have occurred in Turkey’s educational field in recent years should be reflected in the design processes and implementations of educational buildings and they should be regarded as a whole. In elementary school designs, type projects are implemented by the Ministry of Public Works and Settlement. Type project implementation entails a design process which is independent of location and thus can be repeated in multiple sites in various forms. Natural, physical and structural characteristics of the specific location, which constitute the data for the project’s design process, are ignored. This study aims to evaluate and implement energy efficient design principles in the design of elementary schools. In line with this objective, a new approach is proposed to obtain the most appropriate direction dependant facade configuration in terms of climatic and visual comfort conditions in a classroom cubage. In the study, envelope options for this approach which provide climatically and visually optimal conditions depending upon the orientation of Istanbul region are identified. The results obtained are evaluated in terms of energy management. A classroom was taken from the Type Elementary School Projects and the Radiance simulation program was used to calculate the daylight levels achieved in cubage with the existing envelope and in other envelope configurations proposed for different orientations. Based on the assumption that the elementary school was located in Istanbul, daylight levels were calculated for between September and June in the 2006- 2007academic year. In daylight calculations, a characteristic day was determined for each month according to the values obtained from the existing envelope and daylight calculations for the proposed envelope alternatives were designed accordingly on the specified day of the month. Taking into account the period for which shading was desired, external shading instruments were implemented in the proposed orientation-dependent envelope alternatives were developed in accordance with energy efficient design principles. A two-fold position of fixed and movable was adopted for shading instruments. Artificial lighting loads were determined in relation to daylight levels harvested with the existing envelope. In the envelope proposal I with fixed shading instrument, and in the envelope proposal II with movable shading instrument. Energy loads obtained in cubage depending on the orientation variable of envelope alternatives were compared. The results were evaluated from the perspective of lighting economy and visual comfort conditions and were tried to design an appropriate solution. Viewed from the perspective of energy loads, when shading instruments are in a fixed position, monthly artificial lighting energy is slightly more in the east and the south orientation compared to the energy expenditure caused by the existing building envelope. However, when viewed in terms of visual comfort conditions, the absence of a glare problem and the achievement of a homogenous distribution of light are among the positive aspects of fixed shading instruments. In the south orientation, a significant amount of energy saving is achieved in comparison to the existing building envelope. In the case of movable shading instruments, as windows are not shaded except for the period when shading is desired, in east, west and south orientation, significant energy savings can be achieved in monthly energy expenditures caused by artificial lighting systems compared to the existing envelope. Among the proposed alternatives, in the north orientation, due to increased transparency ratio, artificial lighting energy expenditure is lower. Considering the results explained above, when the position of the lighting instruments are automated depending on the effect of the sunlight on the facade, better results can be obtained in terms both of visual and climatic comfort and of lighting, heating/cooling loads. In this context, further studies can be conducted on the optimization of lighting and climatization loads.
An approach to determine facade options in accordance with different orientations in elementary school classrooms from the perspective of lighting energy management
Keywords: Enerji etkin tasarım; aydınlatma enerjisi yönetimi; ilköğretim aydınlatması; Energy efficient design; lighting energy management; elementary school lighting